2006
DOI: 10.1093/humrep/del099
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids during the in vitro transition from bovine morula to blastocyst

Abstract: The preimplantation bovine embryo metabolizes endogenous ROH to RA, which participates in important cell processes. The true extent of the influence of RA is unknown, although the modulation of retinoid metabolism seems to be a means of increasing cell proliferation. This knowledge might be used to improve embryo quality and the efficiency of stem cell derivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 59 publications
2
32
1
3
Order By: Relevance
“…In the present study, ATRA increased the development of Day 8 blastocysts compared with LG treatment and control, although significant differences between ATRA and LG treatment groups were already evident on Day 7. Blastocyst development on Day 7 after ATRA treatment did not differ from that recorded without additives, similar to that obtained in the presence of serum with morulae produced in B2 + Vero cells (Rodríguez et al 2006). However, in a recent paper (Rodríguez et al 2007), blastocyst rates obtained after 48 h treatment of morulae with ATRA-containing medium were similar to those obtained in the control (no additives) group, but lower than those seen in embryos cultured with 0.1 µm LG.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In the present study, ATRA increased the development of Day 8 blastocysts compared with LG treatment and control, although significant differences between ATRA and LG treatment groups were already evident on Day 7. Blastocyst development on Day 7 after ATRA treatment did not differ from that recorded without additives, similar to that obtained in the presence of serum with morulae produced in B2 + Vero cells (Rodríguez et al 2006). However, in a recent paper (Rodríguez et al 2007), blastocyst rates obtained after 48 h treatment of morulae with ATRA-containing medium were similar to those obtained in the control (no additives) group, but lower than those seen in embryos cultured with 0.1 µm LG.…”
Section: Discussionsupporting
confidence: 72%
“…The wide band filters for blue and ultraviolet excitation were used for detection of TUNEL and bisbenzimide staining, respectively. Discrimination between nuclei showing apoptotic or necrotic morphology was based on a previous description (Gjørret et al 2003), as shown in Rodríguez et al (2006). Cells were regarded as apoptotic when they showed both TUNEL labelling and apoptotic morphology.…”
Section: Apoptosis and Necrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine embryos were in vitro produced from slaughterhouse ovaries as previously reported [15]. Presumptive zygotes were cultured in synthetic oviduc fluid (SOF) with 6 g/l BSA at 38.7 8C, 5% CO 2 , 5% O 2 and 90% N 2 .…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
“…PCR was performed with an i-Cycler iQ Real-Time PCR detection System (Bio-Rad, Hercules, CA, USA) as previously reported [15] Primer sequences, PCR traits for target genes, annealing temperature, sizes of the amplified fragments, and GeneBank accession number are shown in Table 1. Data were normalized to histone H2a1 transcript levels [16].…”
Section: Real-time Pcrmentioning
confidence: 99%